Proposta de planejamento estratégico para implantação de uma vitaminosa de açaí na cidade de Abaetetuba-PA - PRAXEDES, Adalberto Malato (2019)
The present work aims to develop a proposal of strategic planning in order to assist the implantation of a vitamina of açaí in the city of Abaetetuba. For the elaboration of this study, a qualitative research was carried out with the objective of analyzing the factors that influence the company's environments, as well as, the behavior of the market. Through a theoretical survey on subjects related to strategic planning and its main methodologies, the main measures necessary for the elaboration of a strategic planning for the implementation of this company were analyzed. The main measures taken were: the analysis of the internal and external environment, elaboration of a SWOT matrix, definition of organizational guidelines and development of action plans to achieve the organizational objectives embellished.